Nailing the situational leadership theory by synthesizing the culture and nature of principals' leadership and roles in school - Cuaresma-Escobar, Krizzette Joy (Linguistics and Culture Review, 2021)
Leadership circulates via the networks of positions that make up organizations. People's resources serve as the medium and currency of leadership. This research focuses on integrating the culture and nature of the principals' leaders and responsibilities in the school while adhering to the situational leadership theory. The descriptive survey technique of research was utilized in this study. Findings show, that principals must also properly manage opportunities. The principal may be an educational expert continually by creatively scientifically integrating ideas, materials, and human resources to meet the demands of time while also being supportive of his subordinates' accomplishments. When working habits and interpersonal connections are shown in the workplace, effectivity occurs.